Health Service Delivery and Utilization in Timor-Leste : A Qualitative Study - World Bank (Washington, DC, 2013)
This report was written as part of a broader Health Sector Review in Timor-Leste currently being undertaken by the World Bank. Timor-Leste struggles with a burden of disease since independence. Poor health is related to environmental sanitation, poverty, food security, a shortage of doctors, and the difficulty of reaching some rural communities. Some problems are specific to Timor-Leste: violence during the Indonesian occupation, the destruction of the health care sector, and a situation of medical pluralism in which long-established practices of traditional healers co-exist with recent biomedical services. One obstacle the health sector faces is client low utilization of health services. The 2003 Demographic and Health Survey (DHS) reports that about a fifth of poor households have never used the health care facility closest to their house. While it is clear that many households are unwilling or unable to access health care, the reasons for these barriers are poorly understood. One aim of this report is to help fill this gap in knowledge by providing contextual information on health seeking behavior. A second aim is to shed light on human resource challenges in the health sector.